2019
DOI: 10.3389/fimmu.2019.01382
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Evolution and Functional Divergence of Lamprey Programmed Cell Death Genes

Abstract: The programmed cell death (PDCD) family plays a significant role in the regulation of cell survival and apoptotic cell death. However, the evolution, distribution and role of the PDCD family in lampreys have not been revealed. Thus, we identified the PDCD gene family in the lamprey genome and classified the genes into five subfamilies based on orthologs of the genes, conserved synteny, functional domains, phylogenetic tree, and conserved motifs. The distribution of the lamprey PDCD family and the immune respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 64 publications
(58 reference statements)
0
29
0
Order By: Relevance
“… 36 Both apoptosis and cell proliferation are precisely regulated by genes to ensure the dynamic balance of the number of cells in the body. 37 It has been found that the damage to articular cartilage and bone tissue in the process of RA is closely related to the excessive proliferation of synovial cells and insufficient apoptosis. 38 , 39 …”
Section: Discussionmentioning
confidence: 99%
“… 36 Both apoptosis and cell proliferation are precisely regulated by genes to ensure the dynamic balance of the number of cells in the body. 37 It has been found that the damage to articular cartilage and bone tissue in the process of RA is closely related to the excessive proliferation of synovial cells and insufficient apoptosis. 38 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…The PBS group was used as a control group. Then, leukocyte RNA was extracted and reversetranscribed with a PrimeScript RT-PCR kit (TaKaRa, China) (34). Importantly, the genomic DNA was removed according to the instructions to eliminate interference.…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%
“…qPCR was performed in triplicate using a TaKaRa PCR Thermal Cycler Dice Real Time System, and L-gapdh (GenBank accession No. KU041137.1) was used as an internal control (28,29,34). The reaction efficiency was tested by the gradual dilution of cDNA template (1x, 5x, 10x, 20x, and 40x).…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%
“…The transition from jawless to jawed vertebrates was caused by some significant evolutionary events, including gene origination and evolution, gene duplication, and cell population and tissue structure changes. Due to its unique evolutionary status, lampreys are essential for exploring the evolution of vertebrates and the origin of different functional mechanisms ( Smith et al, 2018 ; Guan et al, 2019 ). In addition, lampreys are typical migratory organisms that live in the ocean for part of the year.…”
Section: Introductionmentioning
confidence: 99%